Synthesis method for preparing nano-copper catalyst through ball milling method and application of nano-copper catalyst

The preparation of nanocopper catalysts by ball milling method solves the problem of insufficient selectivity and stability in electrocatalyzing CO2 reduction to make C2+ products, and achieves efficient CO2 reduction performance and low-cost preparation method.

CN119571367APending Publication Date: 2025-03-07SHENZHEN INST OF ADVANCED TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411736289.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional Cu-based catalysts have lower selectivity and poor stability when electrocatalyzing CO2 reduction to make C2+ products.

Method used

Nanocopper catalyst was prepared by ball milling method. Nanocopper catalyst was prepared by mixing halogen copper salt with organic solvent, ultrasonic centrifugation was performed and supernatant was extracted, and then mixed with Nafion solution and applied driply to the substrate surface to prepare nanocopper catalyst.

Benefits of technology

The nano-copper catalyst exhibits excellent electrocatalytic CO2 reduction performance, high current density, high Faraday efficiency, and simple preparation method, mild conditions, environmentally friendly and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571367A_ABST
    Figure CN119571367A_ABST
Patent Text Reader

Abstract

According to the synthesis method for preparing the nano-copper catalyst through the ball milling method, the nano-copper catalyst prepared through the ball milling method and the application, halogen copper salt and an organic solvent are mixed and subjected to ball milling, a precursor obtained after ball milling is subjected to ultrasonic centrifugal treatment, supernate is extracted, the supernate and a Nafion solution are mixed and then dropwise coated on the surface of a substrate, and the nano-copper catalyst prepared through the ball milling method is obtained. According to the preparation method, halogen copper salt is taken as a raw material, the nano-copper catalyst containing a nano-Cu elementary substance catalyst is prepared by using a green ball-milling method, due to the high grain boundary density of the unique crystal surface, the spherical nano-copper catalyst shows excellent performance on electrocatalytic CO2 reduction, the reduction reaction current density of the spherical nano-copper catalyst is large, and the spherical nano-copper catalyst can be used as a catalyst for electrocatalytic CO2 reduction. The composite material is high in Faraday efficiency, can be used as an electro-catalysis CO2 reduction catalyst, and has a good application prospect, and the preparation method is simple, mild in condition, environment-friendly and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrocatalysis technology, and in particular to a method for preparing a nano copper catalyst by ball milling, a method for preparing a nano copper catalyst by ball milling, and an application thereof. Background Art

[0002] CO2 is a non-polar linear molecule and a thermodynamically inert molecule. Theoretically, it requires a high temperature of more than 1600K to break the chemical bond (the bond energy of C=O is 783kJ / mol), which makes the activation and reduction of CO2 very difficult. It is usually necessary to introduce highly reducing H2 under high temperature and high pressure conditions to promote the activation of CO2. Among the many CO2 utilization technologies, CO2 can be used to produce a variety of high-value chemicals through catalytic reduction. H2 is usually used as a reducing agent, and light, electricity, heat, etc. are used as energy supplies. Under the action of a catalyst, the highly oxidized carbon in CO2 is reduced to reusable carbon-containing (C1, C 2+ ) Resource products to realize the resource utilization of CO2.

[0003] Compared with thermochemical conversion and photochemical conversion, electrochemical conversion of CO2 has the following advantages: mild reaction conditions, can be carried out at room temperature and pressure; controllable reaction process, by changing the potential, catalyst, electrolyte can adjust the selectivity and generation rate of the product; using electricity generated by renewable energy (wind energy, solar energy, etc.) as the driving force, can achieve carbon neutral cycle; modular reaction system, easy to achieve industrial production. Therefore, the electrochemical conversion of CO2 has great prospects for reducing the concentration of CO2 in the atmosphere.

[0004] CO2 is a stable linear molecule and the ECR process is a multi-step reaction of multiple proton-electron transfer, which converts CO2 into C2 and C 2+ The products are quite difficult to produce. Because copper has a moderate binding strength to the *CO intermediate, the *CO intermediate can further react to produce C2 and C 2+ products, and is therefore the only known metal that can significantly catalyze the conversion of CO2 into multi-carbon products. However, conventional Cu-based catalysts are currently limited in their ability to electrocatalyze CO2 reduction to C 2+ The product has low selectivity and poor stability. Summary of the invention

[0005] In view of this, it is necessary to improve the electrocatalytic CO2 reduction to C 2+ The defects of low selectivity and poor stability of the product are solved by providing a ball milling method for preparing a nano copper catalyst with high selectivity and excellent stability, a synthesis method and an application thereof.

[0006] To solve the above problems, this application adopts the following technical solutions:

[0007] One of the purposes of this application is to provide a method for preparing a nano copper catalyst by ball milling, comprising the following steps:

[0008] The halogen copper salt and the organic solvent are mixed and ball-milled;

[0009] The precursor obtained after ball milling is subjected to ultrasonic centrifugation and the supernatant is extracted;

[0010] The supernatant is mixed with a Nafion solution and then dripped onto the surface of a substrate to obtain the nano copper catalyst prepared by the ball milling method.

[0011] In some of the embodiments, the mass volume ratio of the halogen copper salt to the organic solvent is no more than 1 g / mL.

[0012] In some embodiments, the volume percentage of the supernatant to the Nafion solution is 100:1 to 10:1.

[0013] In some of the embodiments, in the step of mixing and ball-milling the halogen copper salt and the organic solvent, the atmosphere of the ball milling is an inert gas, the grinding balls of the ball mill are composed of large zirconium oxide grinding balls and small zirconium oxide grinding balls, the diameter of the large balls is 8 to 15 mm, the diameter of the small balls is 3 to 5 mm, the number ratio of the large balls to the small balls is 1:0.5 to 1:2, the mass ratio of the grinding balls to the materials is 20:1 to 50:1, the rotation speed is 500 to 1000 rpm, and the ball milling time is not more than 600 min.

[0014] In some of the embodiments, the optimal quantity ratio of the large balls to the small balls is 1:1, and the optimal mass ratio of the grinding balls to the material is 30:1. The appropriate ball milling ratio can weaken the local heating effect and reduce the friction coefficient.

[0015] In some of the embodiments, the halogen copper salt is at least one of monovalent or divalent halogen salts or quasi-halogen salts of copper, and the halogen copper salt is at least one of CuCl2, CuCl, CuBr2, CuBr, CuI2, and CuI.

[0016] In some of the embodiments, the step of ultrasonically centrifuging the precursor obtained after ball milling and extracting the supernatant specifically includes the following steps: placing the precursor obtained after ball milling in a centrifuge tube, adding an organic solvent and centrifuging for 3 times to extract the supernatant, the rotation speed of each centrifugation is 8000-15000rpm, and the time of each centrifugation is 5-15 minutes.

[0017] In some embodiments, the organic solvent is at least one of methanol, ethanol, propanol, isopropanol, butanol, ethyl acetate, acetonitrile, N-methylpyrrolidone, and dimethylformamide.

[0018] In some of the embodiments, in the step of preparing the nano copper catalyst by ball milling method by mixing the supernatant with Nafion solution and then dripping it on the substrate surface to obtain a nano Cu catalyst, the mass ratio of the Nafion solution is 0.05-20wt%.

[0019] The second purpose of the present application is to provide a nano copper catalyst prepared by a ball milling method, which is prepared by the synthetic method for preparing a nano copper catalyst by a ball milling method.

[0020] The third purpose of the present application is to provide an application of the nano copper catalyst prepared by the ball milling method in the electrocatalytic CO2 reduction reaction.

[0021] This application adopts the above technical solution, and its beneficial effects are as follows:

[0022] The present application provides a ball milling method for preparing a nano copper catalyst, a synthesis method and an application. A halogen copper salt and an organic solvent are mixed and ball milled, a precursor obtained after ball milling is subjected to ultrasonic centrifugation and a supernatant is extracted, the supernatant is mixed with a Nafion solution and then drop-coated on a substrate surface to obtain the nano copper catalyst prepared by the ball milling method. The present application uses a halogen copper salt as a raw material and utilizes a green ball milling method to prepare a nano copper catalyst containing a nano Cu single-element catalyst. The nano copper catalyst benefits from the high grain boundary density on the unique crystal surface and exhibits excellent performance in electrocatalytic CO2 reduction. The reduction reaction current density is large and the Faraday efficiency is high. It can be used as an electrocatalytic CO2 reduction catalyst and has a good application prospect. The preparation method is simple, the conditions are mild, it is environmentally friendly and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 This is a flow chart of the steps of the synthetic method for preparing nano copper catalyst by ball milling provided in an embodiment of the present application.

[0025] Figure 2 This is a SEM schematic diagram of the nano copper element prepared by the ball milling method in Example 1.

[0026] Figure 3 This is a bar graph of the Faraday efficiency of the catalyst electrode in Example 1 for catalytic reduction of CO2 to produce ethanol at different current densities.

[0027] Figure 4 The catalyst electrode of Example 1 is CO2 catalytic reduction to produce C 2+ Faraday efficiency bar graph of the product at different current densities. DETAILED DESCRIPTION

[0028] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0029] In the description of the present application, it should be understood that the terms "upper", "lower", "horizontal", "inside", "outside", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0030] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0031] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0032] See also Figure 1 The method for preparing a nano-copper catalyst by ball milling provided in the embodiment of the present application specifically includes the following steps S110 to S130, and its implementation method is described in detail below.

[0033] Step S110: ball-milling the halogen copper salt and the organic solvent.

[0034] In this embodiment, in the step of mixing the halogen copper salt and the organic solvent by ball milling, the atmosphere of the ball milling is an inert gas, the grinding balls of the ball milling are composed of large zirconia grinding balls and small zirconia grinding balls, the diameter of the large balls is 8 to 15 mm, the diameter of the small balls is 3 to 5 mm, the number ratio of the large balls to the small balls is 1:0.5 to 1:2, the mass ratio of the grinding balls to the material is 20:1 to 50:1, the rotation speed is 500 to 1000 rpm, and the ball milling time is not more than 600 min. The inert gas may include Ar or nitrogen. The mass volume ratio of the halogen copper salt to the organic solvent is not more than 1 g / mL.

[0035] Preferably, the quantity ratio of the large balls to the small balls is 1:1, and the mass ratio of the grinding balls to the material is 30:1. An appropriate ball milling ratio can weaken the local temperature rise effect and reduce the friction coefficient.

[0036] In this embodiment, the halogen copper salt is at least one of monovalent or divalent halogen salts or quasi-halogen salts of copper, and the halogen copper salt is at least one of CuCl2, CuCl, CuBr2, CuBr, CuI2, and CuI.

[0037] In this embodiment, the organic solvent is at least one of methanol, ethanol, propanol, isopropanol, butanol, ethyl acetate, acetonitrile, N-methylpyrrolidone, and dimethylformamide.

[0038] Step 120: subjecting the precursor obtained after ball milling to ultrasonic centrifugation and extracting the supernatant.

[0039] In this embodiment, the step of ultrasonically centrifuging the precursor obtained after ball milling and extracting the supernatant specifically includes the following steps: placing the precursor obtained after ball milling in a centrifuge tube, adding an organic solvent and centrifuging for 3 times to extract the supernatant, the rotation speed of each centrifugation is 8000-15000rpm, and the time of each centrifugation is 5-15 minutes.

[0040] In this embodiment, the organic solvent is at least one of methanol, ethanol, propanol, isopropanol, butanol, ethyl acetate, acetonitrile, N-methylpyrrolidone, and dimethylformamide.

[0041] Step S130: mixing the supernatant with the Nafion solution and then dripping the mixture onto the surface of the substrate to obtain the nano copper catalyst.

[0042] In this embodiment, in the step of mixing the supernatant with the Nafion solution and then dripping it on the surface of the substrate to obtain the nano copper catalyst, the mass ratio of the Nafion solution is 0.05-20wt%.

[0043] It can be understood that since the Nafion solution is a solution including isopropanol, isopropanol is an organic substance containing a hydroxyl group, a methyl group and an ethyl group, and has a molecular formula of C3H8O, the reaction between isopropanol and copper can occur at room temperature, and the reaction relationship between them is a redox reaction, in which the copper cation is reduced to a pure metal form of copper, and the isopropanol is oxidized to an aldehyde or an acid.

[0044] The ball milling method provided in the above embodiment of the present application is used to prepare the nano copper catalyst.

[0045] Using halogen copper salts as raw materials, a nano-copper catalyst containing a nano-Cu single-element catalyst was prepared using a green ball milling method. Benefiting from the high grain boundary density on the unique crystal surface, the nano-copper catalyst exhibits excellent performance in electrocatalytic CO2 reduction. Its reduction reaction current density is large and its Faraday efficiency is high. It can be used as an electrocatalytic CO2 reduction catalyst and has good application prospects. The preparation method is simple, the conditions are mild, it is environmentally friendly and the cost is low.

[0046] The above technical solution of the present application is described in detail below in conjunction with specific embodiments.

[0047] Example 1

[0048] The ball milling method provided in this embodiment 1 for preparing the nano copper catalyst comprises the following steps:

[0049] (1) Preparation of ball milling precursor: grinding balls are added to a ball milling jar, followed by addition of 3.384 g of CuBr and 4 mL of an organic solvent, the ball-to-material mass ratio is controlled, and ball milling is performed in a planetary ball mill with a set ball milling program, wherein the grinding balls are composed of large zirconia grinding balls and small zirconia grinding balls, the large balls have a diameter of 8 mm, the small balls have a diameter of 3 mm, the number ratio of the large balls to the small balls is 1 to 1, and the mass ratio of the grinding balls to the material is 30:1. In an Ar atmosphere, the rotation speed is 720 rpm and the ball milling is performed for 600 minutes.

[0050] (2) The precursor obtained by ball milling was then placed in a centrifuge tube, 5 mL of isopropanol organic solvent was added, ultrasonication and centrifugation were performed, and 1 mL of supernatant A was extracted.

[0051] (3) Prepare Nafion solution B: Disperse 10 μL of Nafion in 1000 μL of isopropanol and disperse evenly by ultrasonication;

[0052] (4) The solution A and the solution B in Example 1 were uniformly mixed, and then dripped onto the surface of the YSL carbon paper, dried, and repeatedly dripped 3-5 times. The electrode material of the single nano-copper was prepared, which was marked as Cu-YSL electrode material. Figure 2 This is a SEM schematic diagram of the preparation of nano-copper catalyst by ball milling method provided in Example 1.

[0053] Table 1 shows the electrocatalytic performance of the electrode samples prepared in Example 1 at different voltages

[0054] <![CDATA[Current density / mAcm -2 > 100 300 500 Electrolysis time / h 1.0 1.0 1.0 Ethanol Faradaic efficiency (%) 15.9 27.8 28.6 <![CDATA[C 2+ Product Faradaic efficiency (%)]]> 34.6 53.5 51.4

[0055] See also Figure 3 , is a bar graph of the Faraday efficiency of the catalyst electrode in Example 1 for catalytic reduction of CO2 to produce ethanol at different current densities.

[0056] Example 2

[0057] This embodiment 2 provides a method for preparing a nano copper catalyst by ball milling, comprising the following steps:

[0058] (1) Preparation of ball milling precursor: grinding balls are added to a ball milling jar, followed by addition of 11.5 g of CuBr and 15 mL of an organic solvent, the ball-to-material mass ratio is controlled, and ball milling is performed in a planetary ball mill with a set ball milling program, wherein the grinding balls are composed of large zirconia grinding balls and small zirconia grinding balls, the large balls have a diameter of 15 mm, the small balls have a diameter of 5 mm, the number ratio of the large balls to the small balls is 0.5-1, the mass ratio of the grinding balls to the material is 20:1, and the ball milling is performed for 300 minutes at a rotation speed of 500 rpm in an Ar atmosphere.

[0059] (2) The precursor obtained by ball milling was then placed in a centrifuge tube, 5 mL of isopropanol organic solvent was added, ultrasonication and centrifugation were performed, and 1 mL of supernatant A was extracted.

[0060] (3) Prepare Nafion solution B: Disperse 10 μL of Nafion in 1000 μL of isopropanol and disperse evenly by ultrasonication;

[0061] (4) Solution A and Solution B in Example 1 were uniformly mixed, and dripped onto the surface of the YSL carbon paper, dried, and repeatedly dripped 3-5 times to prepare a nano copper electrode material, which was marked as Cu-YSL electrode material.

[0062] Table 2 shows the electrocatalytic performance of the electrode samples prepared in Example 2 at different voltages

[0063] <![CDATA[Current density / mAcm -2 > 100 300 500 Electrolysis time / h 1.0 1.0 1.0 Ethanol Faradaic efficiency (%) 15.1 25.2 26.9 <![CDATA[C 2+ Product Faradaic efficiency (%)]]> 32.3 51.2 50.6

[0064] Example 3

[0065] This embodiment 3 provides a method for preparing a nano copper catalyst by ball milling, comprising the following steps:

[0066] (1) Preparation of ball milling precursor: Add grinding balls into a ball milling jar, then add 23 g CuBr and 30 mL organic solvent, control the ball-to-material mass ratio, and perform ball milling in a planetary ball mill with a set ball milling program, wherein the grinding balls are composed of large zirconium oxide grinding balls and small zirconium oxide grinding balls, the large ball diameter is 10 mm, the small ball diameter is 4 mm, the number ratio of the large ball to the small ball is 1 to 2, the mass ratio of the grinding balls to the material is 50:1, and the rotation speed is 1000 rpm in a N2 atmosphere for 300 minutes.

[0067] (2) The precursor obtained by ball milling was then placed in a centrifuge tube, 5 mL of isopropanol organic solvent was added, ultrasonication and centrifugation were performed, and 1 mL of supernatant A was extracted.

[0068] (3) Prepare Nafion solution B: Disperse 10 μL of Nafion in 1000 μL of isopropanol and disperse evenly by ultrasonication;

[0069] (4) Solution A and Solution B in Example 1 were uniformly mixed, and dripped onto the surface of the YSL carbon paper, dried, and repeatedly dripped 3-5 times to prepare a nano copper electrode material, which was marked as Cu-YSL electrode material.

[0070] Table 3 shows the electrocatalytic performance of the electrode samples prepared in Example 3 at different voltages

[0071] <![CDATA[Current density / mAcm -2 > 100 300 500 Electrolysis time / h 1.0 1.0 1.0 Ethanol Faradaic efficiency (%) 16.8 28.2 29.3 <![CDATA[C 2+ Product Faradaic efficiency (%)]]> 35.2 55.1 57.2

[0072] Example 4

[0073] This embodiment 4 provides a method for preparing a nano copper catalyst by ball milling, comprising the following steps:

[0074] (1) Preparation of ball milling precursor: Add grinding balls into a ball milling jar, then add 30 g CuBr and 30 mL organic solvent, control the ball-to-material mass ratio, and perform ball milling in a planetary ball mill with a set ball milling program, wherein the grinding balls are composed of large zirconium oxide grinding balls and small zirconium oxide grinding balls, the large ball diameter is 12 mm, the small ball diameter is 5 mm, the number ratio of the large ball to the small ball is 0.5-1, the mass ratio of the grinding balls to the material is 40:1, and the rotation speed is 720 rpm in a N2 atmosphere for 300 minutes.

[0075] (2) The precursor obtained by ball milling was then placed in a centrifuge tube, 5 mL of isopropanol organic solvent was added, ultrasonication and centrifugation were performed, and 1 mL of supernatant A was extracted.

[0076] (3) Prepare Nafion solution B: Disperse 10 μL of Nafion in 1000 μL of isopropanol and disperse evenly by ultrasonication;

[0077] (4) Solution A and Solution B in Example 1 were uniformly mixed, and dripped onto the surface of the YSL carbon paper, dried, and repeatedly dripped 3-5 times to prepare a nano copper electrode material, which was marked as Cu-YSL electrode material.

[0078] Table 4 shows the electrocatalytic performance of the electrode samples prepared in Example 4 at different voltages

[0079]

[0080]

[0081] Example 5

[0082] This embodiment 5 provides a ball milling method for preparing a nano copper catalyst, comprising the following steps:

[0083] (1) Preparation of ball milling precursor: Add grinding balls to a ball milling jar, then add 115 g of CuBr and 120 mL of an organic solvent, control the ball-to-material mass ratio, and perform ball milling in a planetary ball mill with a set ball milling program, wherein the grinding balls are composed of large zirconia grinding balls and small zirconia grinding balls, the large balls have a diameter of 12 mm, the small balls have a diameter of 4 mm, the number ratio of the large balls to the small balls is 0.6 to 1.2, the mass ratio of the grinding balls to the material is 30:1, and the ball milling is performed for 500 minutes at a rotation speed of 800 rpm in a N2 atmosphere.

[0084] (2) The precursor obtained by ball milling was then placed in a centrifuge tube, 5 mL of isopropanol organic solvent was added, ultrasonication and centrifugation were performed, and 1 mL of supernatant A was extracted.

[0085] (3) Prepare Nafion solution B: Disperse 10 μL of Nafion in 1000 μL of isopropanol and disperse evenly by ultrasonication;

[0086] (4) Solution A and Solution B in Example 1 were uniformly mixed, and dripped onto the surface of the YSL carbon paper, dried, and repeatedly dripped 3-5 times to prepare a nano copper electrode material, which was marked as Cu-YSL electrode material.

[0087] Table 5 shows the electrocatalytic performance of the electrode samples prepared in Example 5 at different voltages

[0088] <![CDATA[Current density / mAcm -2 > 100 300 500 Electrolysis time / h 1.0 1.0 1.0 Ethanol Faradaic efficiency (%) 17.3 29.1 28.3 <![CDATA[C 2+ Product Faradaic efficiency (%)]]> 36.1 56.3 57.1

[0089] Comparative Example 1

[0090] Add 10 mL of deionized water to 0.64 g of Cu(NO3)3·5H2O. Subsequently, add 1.0 M KOH to the above solution and stir for 2 h. Wash the resulting precipitate with deionized water three times by ultrasonic and centrifugation, dry at 80 °C overnight, and calcine at 400 °C for 2 h. Take 30 mg of CuO catalyst, add 180 μL of 5% Nafion solution, 3 mL of 2-propanol and ultrasonicate for 30 min, then add dropwise on the surface of YSL carbon paper and dry. Obtain the CuO catalyst electrode material, and perform performance evaluation on the same electrolytic cell under the same operating conditions.

[0091] Table 6 shows the electrocatalytic performance of the catalyst samples prepared in Comparative Example 1 at different voltages

[0092] <![CDATA[Current density / mAcm -2 > 100 300 500 Electrolysis time / h 1.0 1.0 1.0 Ethanol Faradaic efficiency (%) 3.8 6.6 4.9 <![CDATA[C 2+ Product Faradaic efficiency (%)]]> 15.3 16.5 16.9

[0093] Comparative Example 2

[0094] Commercial nano Cu powder (25 nm) was used as primary nanoparticles and calcined at 400°C for 2 h in an argon-hydrogen mixed atmosphere with a hydrogen volume fraction of 10%. The single Cu catalyst electrode material was obtained and the performance was evaluated in the same electrolytic cell under the same operating conditions.

[0095] Table 7 shows the electrocatalytic performance of the electrode samples prepared in Comparative Example 2 at different voltages

[0096] <![CDATA[Current density / mAcm -2 > 100 300 500 Electrolysis time / h 1.0 1.0 1.0 Ethanol Faradaic efficiency (%) 6.5 8.9 13.5 <![CDATA[C 2+ Product Faradaic efficiency (%)]]> 18.6 20.3 24.6

[0097] Effect verification

[0098] The performance of the Cu-based catalyst electrodes of Examples 1-5 and Comparative Examples 1-2 of the present invention was evaluated using a flow cell as a CO2 catalytic reduction reaction device. The specific measurement conditions were:

[0099] The gaseous products were directly detected by online gas chromatography (GC2014, Shimadzu, Japan) with a sampling interval of 20 min, and the liquid products were detected by liquid nuclear magnetic resonance (400 M).

[0100] The performance of the Cu-based catalyst electrodes of Examples 1-5 and Comparative Examples 1-2 of the present invention was evaluated using a gas phase diffusion electrolytic cell as a CO2 catalytic reduction reaction device. The specific measurement conditions were:

[0101] (1) Reference electrode: mercury-mercury oxide electrode;

[0102] (2) Counter electrode: platinum electrode;

[0103] (3) Working electrode: Cu-based composite electrode (1×1cm 2 );

[0104] (4) Electrolyte: 1 M KOH solution;

[0105] (5) Ion exchange membrane: Fumasep FAA-3-PK-130;

[0106] (6) CO2 flow rate: 20 sccm;

[0107] Faraday efficiency (FE) calculation:

[0108] For gaseous products, we usually use gas chromatograph for quantitative analysis. The Faraday efficiency calculation formula is: in:

[0109] In the formula, z is the number of transferred electrons; F is the Faraday constant (96485C·mo1 -1 ); C is the concentration of the product (ppm×10 -6 ); v is the gas flow rate into the chromatogram (m 3 ·s -1 ); P is the pressure of the chromatographic injection loop (Pa); j is the current density (A); R is the ideal gas constant (8.314 J·mol -1 ·K -1 );T is the temperature of the chromatographic injection loop (K).

[0110] like Figure 4 As shown in Example 1 and Comparative Example 1, it can be seen that the nano-element Cu catalyst provided by the present invention is used for CO2 electroreduction to produce C 2+ During the product process, while maintaining a high liquid product ethanol selectivity (more than 30%), C 2+ The overall selectivity also exceeded 50%.

[0111] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.

Claims

1. A method for preparing a nano copper catalyst by ball milling, characterized in that: The steps include: The halogen copper salt and the organic solvent are mixed and ball-milled; The precursor obtained after ball milling is subjected to ultrasonic centrifugation and the supernatant is extracted; The supernatant is mixed with a Nafion solution and then drop-coated on the surface of a substrate to obtain the nano copper catalyst.

2. The method for preparing a nano copper catalyst by ball milling as claimed in claim 1, characterized in that: The mass volume ratio of the halogen copper salt to the organic solvent is no more than 1 g / mL.

3. The method for preparing a nano copper catalyst by ball milling as claimed in claim 1, characterized in that: The volume percentage of the supernatant to the Nafion solution is 100:1 to 10:

1.

4. The method for preparing a nano copper catalyst by ball milling as claimed in claim 1, characterized in that: In the step of mixing the halogen copper salt and the organic solvent and ball milling, the atmosphere of the ball milling is an inert gas, the grinding balls of the ball milling are composed of large zirconium oxide grinding balls and small zirconium oxide grinding balls, the diameter of the large balls is 8 to 15 mm, the diameter of the small balls is 3 to 5 mm, the number ratio of the large balls to the small balls is 1:0.5 to 1:2, the mass ratio of the grinding balls to the materials is 20:1 to 50:1, the rotation speed is 500 to 1000 rpm, and the ball milling time is not more than 600 min.

5. The method for preparing a nano copper catalyst by ball milling as claimed in claim 4, characterized in that: The optimal quantity ratio of the large balls to the small balls is 1:1, and the optimal mass ratio of the grinding balls to the material is 30:

1.

6. The method for preparing a nano copper catalyst by ball milling as claimed in claim 1 or 2, characterized in that: The halogen copper salt is at least one of monovalent or divalent halogen salts or quasi-halogen salts of copper, and the halogen copper salt is at least one of CuCl2, CuCl, CuBr2, CuBr, CuI2, and CuI.

7. The method for preparing a nano copper catalyst by ball milling as claimed in claim 1, characterized in that: The step of subjecting the precursor obtained after ball milling to ultrasonic centrifugation and extracting the supernatant specifically includes the following steps: placing the precursor obtained after ball milling in a centrifuge tube, adding an organic solvent and centrifuging for 3 times to extract the supernatant, the rotation speed of each centrifugation is 8000-15000rpm, and the time of each centrifugation is 5-15 minutes.

8. The method for preparing a nano copper catalyst by ball milling as claimed in claim 1 or 7, characterized in that: The organic solvent is at least one of methanol, ethanol, propanol, isopropanol, butanol, ethyl acetate, acetonitrile, N-methylpyrrolidone and dimethylformamide.

9. The method for preparing a nano copper catalyst by ball milling as claimed in claim 1, characterized in that: In the step of mixing the supernatant with the Nafion solution and then dripping it on the surface of the substrate to obtain the nano copper catalyst prepared by the ball milling method, the mass ratio of the Nafion solution is 0.05-20wt%.

10. A method for preparing a nano copper catalyst by ball milling, characterized in that: The nano copper catalyst is prepared by the synthetic method for preparing the nano copper catalyst by ball milling as described in any one of claims 1 to 9.

11. Use of the nano copper catalyst prepared by the ball milling method as claimed in claim 10 in electrocatalytic CO2 reduction reaction.